Complete Penetrance but Different Phenotypes in a Korean Family with Maternal Interstitial Duplication at 15q11.2-q13.1: A Case Report - Ji Yoon Han; Hyun Joo Lee; Young-Mock Lee; Joonhong Park (MDPI AG, 2021)
The 15q duplication syndrome (dup15q) is due to the presence of at least one additional derived copy of the Prader-Willi syndrome/Angelman syndrome (PWS/AS) critical region that is approximately 5 Mb long within chromosome 15q11.2-q13.1. This report describes distinct roles of the origin of interstitial (int) dup15q underlining the critical importance of maternally active imprinted genes in the contribution to complete penetrance but different phenotypes of neuropsychotic disorders such as schizophrenia (SCZ) and autism spectrum disorder (ASD) in a Korean family. The proband's mother as a consultant visited our hospital for her offspring's genetic counseling and segregation analysis. She had two daughters diagnosed as SCZ or ASD and one son diagnosed as ASD. To resolve the potential genetic cause of SCZ and ASD in the proband and her sibling, whole genomic screening of chromosomal rearrangements by array-comparative genomic hybridization (CGH) was performed using SurePrint G3 Human CGH + SNP Microarray 4 × 180 K. Results of the array-CGH analysis revealed an interstitial duplication at 15q11.2-q13.1 (duplication size of 5.4 Mb) in the mother and her three offspring with SCZ or ASD. Our case, together with previous findings of high occurrence of psychotic disorder, suggest that maternally expressed gene product in the critical region of PWS/AS might mediate the risk of neurodevelopmental disorder (ASD) as well as psychotic disorder (SCZ). Multiple cytogenetic and molecular methods are recommended for investigating children with 15q11.2-q13.1 duplication and neuropsychotic disorders.